2023
DOI: 10.3390/beverages9020037
|View full text |Cite
|
Sign up to set email alerts
|

From Fermented Wash to New Make Spirit: Assessing the Evolution of Flavour Characteristics of Scotch Whisky Using Lab-Scale Process Simulations

Abstract: New product development for distilled spirits frequently involves experimental trials at the laboratory scale that attempt to replicate industrial-scale production processes. This process is time-consuming and limits the number of samples that can be analysed. The aim of the present study was to conduct laboratory-scale Scotch malt whisky production experiments to determine if samples taken from earlier in the production process, that is, directly after fermentation (wash stage) or after a single distillation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Recent findings comparing the flavour profile of wash, low wines, and new make spirit of different yeast strains showed that the key flavour notes are stable throughout these production steps. This finding will support the development of new yeast strains by reducing the time needed for sample preparation by eliminating the need for a double distillation for early yeast screening rounds (Daute et al 2023 ). Together with the finding that congener profiling of wort by gas chromatography–mass spectrometry (GC–MS) gives comparable data to the sensory evaluation, this could further reduce the time by not requiring a sensorial evaluation of samples in early screening steps (Daute et al 2021b ).…”
Section: Yeast Strain Improvementmentioning
confidence: 79%
“…Recent findings comparing the flavour profile of wash, low wines, and new make spirit of different yeast strains showed that the key flavour notes are stable throughout these production steps. This finding will support the development of new yeast strains by reducing the time needed for sample preparation by eliminating the need for a double distillation for early yeast screening rounds (Daute et al 2023 ). Together with the finding that congener profiling of wort by gas chromatography–mass spectrometry (GC–MS) gives comparable data to the sensory evaluation, this could further reduce the time by not requiring a sensorial evaluation of samples in early screening steps (Daute et al 2021b ).…”
Section: Yeast Strain Improvementmentioning
confidence: 79%